Open Dislocation of the Lunate and Triquetrum: A Case Report - Kang, Gavrielle Hui-Ying; Teoh, Lam Chuan (Journal of Hand and Microsurgery, 2023)
The Mayfield sequence of progressive perilunar instability is commonly encountered. A reverse-perilunate sequence has also been described, where forces are transmitted from the ulnar wrist, resulting in progressive disruption of the ulnocarpal and lunotriquetral intervals. A concomitant dislocation of both the lunate and triquetrum together is a rare injury and has not been reproduced in cadaver models nor widely encountered in clinical cases. We report a rare case of an open volar dislocation of the lunate and triquetrum, and outline the management principles and outcomes in our patient. This case highlights that not all perilunar injuries occur in the conventional sequence. Differing paths of force transmission may result in atypical patterns of carpal disruption. Nonetheless, the broad management principles are similar. Achieving carpal reduction and stabilization, soft-tissue coverage, and early rehabilitation results in reasonable patient outcomes.
Keywords: perilunate dislocation; carpal dislocation; wrist dislocation